Edukasi gizi seimbang sejak dini pada anak prasekolah sebagai upaya pencegahan masalah stunting - Djamaludin, Djunizar; Aryastuti, Nurul; Nadila, Tiya; Hidayanti, Sisca; Hasanah, Uswatun (JOURNAL OF Public Health Concerns, 2023)
Introduction: The problem of stunting nutrition can not only be intervened in the first thousand days of life (1000 HPK) but can still be intervened at pre-school age to school age and adolescents so that the impact does not get worse to the next stage. Therefore, various efforts need to be made to prevent this nutritional problem from being overcome. One of the efforts that can be done is nutrition education to parents, children, and schools from an early age in the community. This educational activity is part of community service activities. Purpose: This counseling aims to increase the knowledge and attitudes of mothers, children, and teachers in the application of balanced nutritious food consumption in children from an early age. This is an effort to prevent and overcome sustainable stunting at school age in the Pinang Jaya Region. Method: The intervention method used to achieve this goal is interactive counseling using audio-visual counseling media. A total of 40 participants attended Results: After the counseling activities, it was found that all participants, both mothers and children, experienced an increase in knowledge related to the application of balanced nutrition in children's daily menus by an average of 80%. Conclusion: From the results of the counseling, it was concluded that there was a need for mentoring activities from the puskesmas to provide nutrition education to pre-school and school children as well as monitoring the nutritional status of children in schools so that children avoid nutritional problems and have good nutritional status.   Keywords: Children; Education; Stunting; Preschool.   Pendahuluan: Masalah gizi stunting tidak hanya dapat diintervensi pada seribu hari pertama kehidupan (1000 HPK) namun masih bisa dilakukan intervensi pada usia pra sekolah hingga usia sekolah dan remaja agar tidak semakin parah dampaknya ke tahap selanjutnya. Oleh karena itu, berbagai upaya perlu dilakukan untuk mencegah agar masalah gizi ini dapat diatasi. Salah satu upaya yang dapat dilakukan adalah edukasi gizi kepada orangtua, anak, dan pihak sekolah sejak dini di masyarakat. Kegiatan edukasi ini merupakan bagian dari kegiatan pengabdian kepada masyarakat. Tujuan: penyuluhan ini bertujuan untuk meningkatkan pengetahuan dan sikap ibu, anak, dan guru dalam penerapan konsumsi makanan bergizi seimbang pada anak sejak usia dini. Hal ini sebagai upaya mencegah dan mengatasi stunting yang berkelanjutan pada usia sekolah di Wilayah Pinang Jaya. Metode: Metode intervensi yang dilakukan untuk mencapai tujuan tersebut adalah dengan penyuluhan interaktif menggunakan media penyuluhan audio visual. Sebanyak 40 peserta yang hadir Hasil: Setelah kegiatan penyuluhan diperoleh hasil bahwa seluruh peserta baik ibu, dan anak mengalami peningkatan pengetahuan terkait penerapan gizi seimbang pada menu harian anak dengan rata-rata sebesar sebesar 80%. Simpulan: Dari hasil penyuluhan disimpulkan bahwa perlu adanya kegiatan pendampingan dari puskesmas untuk memberikan edukasi gizi pada anak pra sekolah dan anak sekolah serta monitoring status gizi anak di sekolah agar anak terhindar dari masalah gizi dan memiliki status gizi yang baik.